2012
DOI: 10.5999/aps.2012.39.4.412
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Review of Iatrogenic Skin and Soft Tissue Injuries

Abstract: BackgroundEven though the quality of medical and surgical care has improved remarkably over time, iatrogenic injuries that require surgical treatment including injuries caused by cast and elastic bandage pressure, extravasation, and dopamine-induced ischemia still frequently occur. The goal of this study was to estimate the incidence and analyze the distribution of iatrogenic injuries referred to our department.MethodsA retrospective clinical review was performed from April 2006 to November 2010. In total, 196… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…Only a few studies have suggested wound manage procedures [8,[13][14][15][16][17]. Extravasation events involve severe complications such as the progression of a relatively mild wound (tissue edema, redness, or vasculitis) to skin necrosis or an abscess [18]. Despite the high prevalence of extravasation events and their severity, it seems that many medical teams do not know which intravenous fluid leads to severe consequences, which requires early intervention, and which treatment should be administered.…”
Section: Original Articlementioning
confidence: 99%
“…Only a few studies have suggested wound manage procedures [8,[13][14][15][16][17]. Extravasation events involve severe complications such as the progression of a relatively mild wound (tissue edema, redness, or vasculitis) to skin necrosis or an abscess [18]. Despite the high prevalence of extravasation events and their severity, it seems that many medical teams do not know which intravenous fluid leads to severe consequences, which requires early intervention, and which treatment should be administered.…”
Section: Original Articlementioning
confidence: 99%
“…12 Approximately 81% of the cases of digital ischemia caused by vasopressors require amputation, with the remaining having delayed wound healing and minor necrosis. 13 Upper extremity ischemia due to thromboembolism Upper extremity ischemia related to cardiac abnormalities is frequently due to thromboembolism, most commonly from atrial fibrillation, which accounts for approximately 80% of upper extremity thromboembolism. Other less frequent causes include valvular abnormalities, cardiomyopathy, and atrial septal defects.…”
Section: Upper Extremity Ischemiamentioning
confidence: 99%
“…Dear Editors, An iatrogenic wound can be defined as a wound that is attained during or as a result of medical treatment provided by a health care giver. A study by Lee et al reported that the most common iatrogenic injuries that are referred to plastic surgeons are extravasation injuries, followed by cast-induced injuries and vasopressor-induced necrosis (1).…”
Section: Iatrogenic Pressure Sores: Primum Non Nocerementioning
confidence: 99%
“…A study by Lee et al reported that the most common iatrogenic injuries that are referred to plastic surgeons are extravasation injuries, followed by cast-induced injuries and vasopressor-induced necrosis (1).…”
mentioning
confidence: 99%